An electrochemical compatibility investigation of RTIL-based electrolytes with Si-based anodes for advanced Li-ion batteries. (March 2023) - Falco, M.; Lingua, G.; Destro, M.; Silvestri, L.; Meligrana, G.; Lin, R.; Fantini, S.; Maresca, G.; Paolone, A.; Brutti, S.; Appetecchi, G.B.; Elia, G.A.; et al.
Abstract: Silicon is amongst the most attractive anode materials for Li-ion batteries because of its high gravimetric and volumetric capacities; importantly, it is also abundant and cheap, thus sustainable. For a widespread practical deployment of Si-based electrodes, research efforts must focus on significant breakthroughs to addressing the major challenges related to their poor cycling stability. In this work, we focus on the electrolyte-electrode relationships to support the scientific community with a systematic overview of Si-based cell design strategies reporting a thorough electrochemical study of different room temperature ionic liquid (RTIL)-based electrolytes, which contain either lithium bis(fluorosulfonyl)imide (LiFSI) or lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). Their galvanostatic cycling performances with mixed silicon/graphite/few-layer graphene electrodes are evaluated, with first cycle Coulombic efficiency approaching 90% and areal capacity ≈2 mAh/cm 2 in the limited cut-off range of 0.1–2 V vs. Li + /Li 0 . The investigation evidences the superior characteristics of the FSI-based RTILs with respect to the TFSI-based one, which is mostly associated with the superior SEI forming ability of FSI-based systems, even without the use of specific additives. In particular, the LiFSI-EMIFSI electrolyte composition shows the best performance in both Li-half cells and Li-ion cells in which the Si-based electrodes are coupled with 4V-class composite NMC-based cathodes. Highlights: Systematic electrochemical study of Si-based anodes with ionic liquid (RTIL)-based electrolytes. Stable galvanostatic cycling with mixed Si/graphite/graphene up to 1500 mAh/gSi at 20 °C. Superior characteristics of FSI- vs. TFSI-based RTILs due to superior SEI forming ability. Stable cycling in Li-ion cells with Si-based electrodes coupled with 4V-class NMC cathodes. Promising prospects for improving the cyclability of Si–C based anode materials.